Corrosion Inhibition Efficiency Investigation of Yttrium Oxide Nanoparticles Coated on Carbon Steel Alloy - Maha J. Hassin; Taghried A. Salman (مجلة بغداد للعلوم, 2023)
Metal oxide nanoparticles demonstrate uniqueness in various technical applications due to their suitable physiochemical properties. In particular, yttrium oxide nanoparticle(Y2O3NPs) is familiar for technical applications because of its higher dielectric constant and thermal stability. It is widely used as a host material for a variety of rare-earth dopants, biological imaging, and photodynamic therapies. In this investigation, yttrium oxide nanoparticles (Y2O3NPs) was used as an ecofriendly corrosion inhibitor through the use of scanning electron microscopy (SEM), Fourier transforms infrared spectroscopy (FT-IR), UV-Visible spectroscopy, X-ray diffraction (XRD), and energy dispersive X-ray spectroscopy(EDX), the physico-chemical characterization of Y2O3NPs was examined. The primary characteristic peak of YOY at 565 cm-1, which indicates the synthesis of nanoparticles, is seen in the FT-IR spectra. The XRD pattern showed that a single phase cubic structure of YONPs with an Ia-3 space group had formed. SEM was used to examine the surface morphology. The composition of Yttrium and oxygen in Y2O3NPs was determined to be 78.74% and 21.26%, respectively, according to the EDX results. The anticorrosive behavior was tested by polarization curve in 18.204% CaCl2 solution at five temperatures in the range 293- 313 K. Various concentrations 0.15 0.26 and 0.37 of N Y2O3NPs coating on the carbon steel surface were applied using the electrophoresis deposition method. The obtained results indicated that Y2O3NPs formed a protective film acts as a physical barrier for the protection of steel alloy. Additionally, corrosion protection efficiency values of 0.26 N Y2O3NPs coating were superior to that of 0.15 and 0.37 N Y2O3NPs coating, respectively.